Hybridization detection and ancestry estimation among Tupaia glis phylogroups - Jayaraj V.K; Shahrul Anuar Mohd Sah; Ahmad Sofiman Othman (2016)
Previous studies have indicated that Tupaia glis is a composite species with two more additional species that have yet to be named. This study examines eight microsatellite primers developed previously to detect the possibility of hybridisation among the three T. glis phylogroups in Peninsular Malaysia. A total of 140 individuals T. glis were score for microsatellite motifs, of which 70 were used for determining a priori groupings using the assignment test in STRUCTURE. The remaining 70 individuals were then used to test the accuracy of these priori groupings, follwed by ancestry estimation. The results shows that the a priori grouping was accurate in assigning all individuals into three groups and all 140 T. glis individuals were grouped into these distinct groups. While individual groups from Penang Island (T. glis phylogroup 1) were isolated from both T. glis phylogroup 2 and 3, sharing of alleles in some individuals of T. glis phylogroup 2 and 3, indicates possible introgression which may have consequences on the survival of the T. glis phylogroup 3.